Phenomenological study: bilingual teaching classroom of Malaysian community colleges - Mohd Noor, Faridatuljana; Harun, Hairuddin (Elsevier Science Ltd, 2015)
The study of bilingual teaching classroom of Malaysian community colleges was designed for developing a brand new environment of teaching in a classroom. It was also to find the main factors that lead to this crucial phenomenon of bilingual classroom. This study has never been conducted among the academicians of community colleges and this is the first study invented by the researcher in order to help in creating new environment of teaching in a bilingual classroom and also to equip learners with good command of English language as to produce trainers who are proficient in the language. The targeted respondents of this study were several course content instructors from several different programs of Malaysian community colleges. Students from semester four undertaking certificate courses from various disciplines of studies were also involved in this research. Non-structured interviews, non-participant observation and note taking were the methods used in this research. The result indicates various answers given by the respondents from the interviews. The needs of the language for each classroom are highly depend on the teachers’ competencies of the language used instead of the learners’ needs. In a nutshell, the bilingual teaching classroom of community colleges can be evaded by practicing better approaches and methods in teaching.